Very Rapid Resolution of Posttraumatic Acute Subdural Hematoma in a 2-Year-Old Girl: A Case Report - Singh, Jasmit; Kharosekar, Hrushikesh; Velho, Vernon (Indian Journal of Neurotrauma, 2015)
The diagnosis and management of acute subdural hematoma is important in neurosurgery practice as it is encountered in 10 to 20% of the severe traumatic brain injury cases. Rapid spontaneous resolution of acute subdural hematoma within few hours is seen rarely on the computed tomography scan. We present a case of 2-year-old girl in whom acute subdural hematoma resolved spontaneously within hours of injury.
Keywords: acute subdural hematoma; resolution; spontaneous; conservative management; midline shift